Eye–Hand Coordination Impairment in Glaucoma Patients - Teresa Zwierko (International Journal of Environmental Research and Public Health, 2019)
This study examined whether patients with glaucoma exhibit differences in eye−hand coordination tasks compared to age-matched normal-sighted control subjects. Twenty-eight patients with moderate-to-advanced stages of glaucoma and 28 subjects with no ocular disease participated in the study. The Motor Performance Series (MLS) of the Vienna Test System including aiming, linear tracking, tremor, and tapping tests were used to assess eye−hand coordination. Monocular Humphrey Visual Field and binocular Humphrey Esterman Visual Field tests were used to estimate visual field (VF) defect severity. Correlation between MLS scores and VF defects, visual acuity, and patient age were assessed. Glaucoma patients performed slower aiming at targets, committed more errors, and took longer to complete linear tracking and tremor tasks compared to the normal-sighted control group. Furthermore, tapping test scores indicated reduced hand movements at maximum frequency. The presence of asymmetrical monocular VF defects were associated with longer error durations in linear tracking tasks. Furthermore, MLS scores decline with advancing age and reduced visual acuity. Glaucoma patients had lower values for most MLS parameters compared to controls. However, monocular and binocular VF defects cannot fully explain the impartments in eye−hand coordination associated with glaucoma.